Auditorium Building (Meany Hall), approximately 1912
The Auditorium Building was used for concerts, speeches and other gatherings during the Alaska-Yukon-Pacific Exposition. After the Exposition the building was called Meany Hall. It was demolished in 1965 after receiving earthquake damage. PH Coll 1226.3